2001
DOI: 10.1074/jbc.m011021200
|View full text |Cite
|
Sign up to set email alerts
|

Redox-sensitive Transactivation of Epidermal Growth Factor Receptor by Tumor Necrosis Factor Confers the NF-κB Activation

Abstract: Cross-communication between different signaling systems allows the integration of the great diversity of stimuli that a cell receives under varying physiological situations. In this paper we have explored the possibility that tumor necrosis factor (TNF) receptor signal cross-talks with epidermal growth factor (EGF) receptor signal on the nuclear factor-B (NF-B) activation pathway. We have demonstrated that overexpression of the EGF receptor (EGFR) in NIH3T3 cells significantly enhances TNF-induced NF-B-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 51 publications
3
49
0
Order By: Relevance
“…Recently, TNF-a and EGF signalling pathways have been found to play a physiological function in TNF-a signalling (Hirota et al, 2001). It has been suggested that proteolytic release of transforming growth factor-a, one of the EGFR ligands, is one possible mechanism of EGFR transactivation by TNF-a (Argast et al, 2004;Chen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TNF-a and EGF signalling pathways have been found to play a physiological function in TNF-a signalling (Hirota et al, 2001). It has been suggested that proteolytic release of transforming growth factor-a, one of the EGFR ligands, is one possible mechanism of EGFR transactivation by TNF-a (Argast et al, 2004;Chen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that EGFR transactivation is responsible for the Erk pathway activation that occurs in TPA-induced IL-1␣ synthesis. (41,42), and it has been reported that IL-1␤-induced Erk activation and subsequent MMP-1 expression in human keratinocytes requires EGFR activity (43). Given these observations, we investigated whether inhibition of the EGFR had any effect on induction of IL-1␣ or on activation of IL-1␣-dependent signaling in our system.…”
Section: Activity Of the Epidermal Growth Factor Receptor Is Requiredmentioning
confidence: 99%
“…The other interesting finding was that when cells were also treated with GSE in PD98059+EGF study, they showed comparable DNA synthesis inhibition (82%) as observed in PD98059+GSE treatment, again suggesting an additional inhibitory effect of GSE on DNA synthesis possibly by inhibiting EGF-induced activation of an unidentified MEK1-independent mitogenic response. With regard to an additional mitogenic signaling by EGF independent of MEK1, in a recent study, it has been shown that EGFR activation through redox mechanism activates NF-kB independent of MEK1 (Hirota et al, 2001). It is also important to emphasize that NF-kB is constitutively active in DU145 PCA cells (Palayoor et al, 1999), and so does EGFR-ligand autocrine growth loop (Hirota et al, 2001).…”
Section: Grape Seed Extract Modulates Mapks In Prostate Cancer Cellsmentioning
confidence: 99%
“…With regard to an additional mitogenic signaling by EGF independent of MEK1, in a recent study, it has been shown that EGFR activation through redox mechanism activates NF-kB independent of MEK1 (Hirota et al, 2001). It is also important to emphasize that NF-kB is constitutively active in DU145 PCA cells (Palayoor et al, 1999), and so does EGFR-ligand autocrine growth loop (Hirota et al, 2001). Whether the observed increase in DNA synthesis by EGF in the presence of MEK1 inhibitor is because of NF-kB activation, remained to be established; however, in our ongoing studies, we observed strong inhibition of constitutively active NF-kB in DU145 cells by GSE (unpublished data).…”
Section: Grape Seed Extract Modulates Mapks In Prostate Cancer Cellsmentioning
confidence: 99%